Projeto - Vida de formiga - Ferrari, Fabiana; Matins, Maysa de Souza; Ávila, Lúcia Helena de Souza; Miotto, Jesuína Aparecida; Foresti, Nélci Nogueira; Oliveira, Maria Auxiliadora de; Santos, Marlene Alves; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF